Cause-Effect Relationships between Painful TMD and Postural and Functional Changes in the Musculoskeletal System: A Preliminary Report - Adam Andrzej Garstka; Monika Brzózka; Aleksandra Bitenc-Jasiejko; Roman Ardan; Helena Gronwald; Piotr Skomro; Danuta Lietz-Kijak (Pain Research and Management)
Introduction. Temporomandibular disease (TMD) is a general term including a group of conditions that cause pain and dysfunction in the masticatory muscles, the temporomandibular joint (TMJ), and their related structures. The painful forms of these dysfunctions have become an increasing phenomenon among dental patients. A number of scientific publications indicated the relationship between the presence of postural dysfunctions and functional disorders of the masticatory system in humans. Nevertheless, dental procedures still very rarely include comprehensive diagnostics and procedures aimed at the normalization of the locomotor system related to TMD. Scientific literature usually refers to and describes the coexistence of postural disorders in patients with TMD in the context of anatomical connections, the so-called biokinematic chains, indicating specific types of postures that correlate with different positions of the mandible and/or teeth. Objective. The aim of the study was to investigate the effect of painless positioning of the mandibular head in the articular fossa on postural and functional changes in the musculoskeletal system. Materials and Methods. The study was conducted on a group of 30 randomly selected patients who reported to the Department of Propaedeutic, Physical Diagnostics and Dental Physiotherapy of the Pomeranian Medical University in Szczecin (Poland). Before the examination, the dentists and the physiotherapist were calibrated by an examiner who had previously been calibrated and had three years of experience in the management of patients with TMD. Training of the appropriate palpation strength was performed, and then the results were discussed. In the study group, painful disorders in the temporomandibular joint with an abnormal position of the mandibular head in the articular fossa and individual posture defects were found. The patients complained of pain in the area of the TMJ, episodes of locked joints, and difficulty biting. None of them was treated for these disorders, previously rehabilitated or participated in any body posture examination. The patients were examined by an interdisciplinary team who also performed a preliminary test. The inclusion criterion for the study group was the presence of TMD symptoms in the past. Myofascial pain was diagnosed on the basis of diagnostic criteria for temporomandibular disorders (RDC/TMD Ia and Ib). On the other hand, the displacement of the articular disc was diagnosed on the basis of the diagnostic criteria of temporomandibular disorders (RDC/TMD IIa)—displacement of the articular disc without reduction. At the same time, the body posture was assessed by inspection and using computer techniques while standing and during motion. The examinations were repeated after positioning the mandibular heads in the articular fossa and stabilizing the condylar process using a temporary silicone occlusal splint. Since there is no DC/TMD protocol in Polish to date, RDC/TMD was used in the study. Results. Initial pilot studies and the authors’ observations indicated that the positioning of the mandibular heads in the articular pits and stabilization of the condylar process by providing the oral cavity with a temporary, silicone occlusive splint significantly influenced the posture of the examined patients, both while standing and during locomotion. This correlation also applies to the corrective effect on the foot architecture during standing and patient gait. Conclusions. Diagnostic and therapeutic management in the course of TMD should be holistic. Nevertheless, the observed changes are often varied and largely dependent on individual posture defects, which is an important postulate for further research on a larger study group.